Beyond the Warren Court and Its Conservative Critics: Toward a Unified Theory of Constitutional Criminal Procedure - Dripps, Donald A. (1990)
Part I develops more fully the differences that divide liberal and conservative commentators on criminal procedure, taking special note of the series of Reports prepared by the Justice Department's Office of Legal Policy and published recently in the University of Michigan Journal of Law Reform. Part II explains my disquiet with the suggestion that original-meaning jurisprudence ought to guide criminal procedure doctrine. Part II also defends the thesis that the fourteenth amendment protects the individual interest in freedom from unjust punishment, rather than any abstract interest in truth for its own sake. Part III considers two familiar controversies in criminal procedure-the fourth amendment exclusionary rule and confessions-from the revised perspective developed in Part II. Part IV adumbrates some possible applications of the revised perspective to trial procedure. These possibilities illustrate that the risk of unjust punishment remains very far from irreducible and that the fourteenth amendment authorizes measures to move this risk closer to its practical minimum